Synthesis of Silicon/Silica/Carbon Composite from Rice Husk via Mechanical Milling Method as Anode Lithium-Ion Batteries - Ramdhan, Mohamad Alief; Muliawati, Nindya Tri (Universitas Pendidikan Mandalika, 2025)
Silicon (Si) and silicon dioxide (SiOâ‚‚), with high theoretical capacities of 4200 mAh gâ»Â¹ and 1965 mAh gâ»Â¹ respectively, have attracted considerable interest as potential anode materials for lithium-ion batteries (LIBs), especially when derived from abundant and renewable sources like rice husk (RH). However, their practical applications are hindered by major challenges, such as significant volume expansion (100%â€“300%) during charge/discharge cycles and inherently low electrical conductivity ( 10â»Â¹ S mâ»Â¹). This study aims to develop a low-cost, sustainable, and high-performance Si/SiOâ‚‚/C composite anode material from rice husk using a combination of mechanical milling and AlClâ‚ƒ/NaCl-activated aluminothermic reduction. The work specifically explores the effects of single-step versus two-step milling processes on the structural integrity and electrochemical performance of the resulting composites. The two-step milling method, a relatively new and more controlled approach, effectively eliminated unwanted metal oxide by-products, as confirmed by X-ray diffraction (XRD) analysis. In contrast, the single-step process resulted in residual impurities. Electrochemical tests revealed that the two-step Si/SiOâ‚‚/C composite delivered a significantly higher specific capacity of 280.01 mAh gâ»Â¹ after 50 cycles, compared to 146.15 mAh gâ»Â¹ from the single-step method. These results highlight the potential of rice husk-derived Si/SiOâ‚‚/C composites as eco-friendly and efficient anode materials for next-generation LIBs.